Tetrahydrobiopterin Supplementation Improves Endothelial Function But Does Not Alter Aortic Stiffness in Patients With Rheumatoid Arthritis - Kaisa M. Mäki‐Petäjä; Lisa Day; Joseph Cheriyan; Frances C. Hall; Andrew J. K. Östör; Nicholas Shenker; Ian B. Wilkinson (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundRheumatoid arthritis is a systemic inflammatory condition associated with increased cardiovascular risk that may be due to underlying endothelial dysfunction and subsequent aortic stiffening. We hypothesized that supplementation with tetrahydrobiopterin (BH4) would recouple endothelial nitric oxide synthase and thus improve endothelial function and consequently reduce aortic stiffness. Methods and ResultsWe conducted 2 randomized, double‐blinded, placebo‐controlled crossover studies examining 2 separate regimens: an acute regimen, with a single dose of BH4 400 mg versus placebo (n=18), and a short‐term regimen, composed of a 1‐week treatment with BH4 400 mg once daily versus placebo (n=15). Flow‐mediated dilatation and aortic pulse wave velocity were studied 4 times, before and after each treatment phase. Acute BH4 supplementation led to an improvement of flow‐mediated dilatation, whereas placebo had no effect (mean±SD of effect difference 2.56±4.79%; P=0.03). Similarly, 1‐week treatment with BH4 improved endothelial function, but there was no change with placebo (mean±SD of effect difference 3.50±5.05%; P=0.02). There was no change in aortic pulse wave velocity following acute or short‐term BH4 supplementation or placebo (mean±SD of effect difference: acute 0.09±0.67 m/s, P=0.6; short‐term 0.03±1.46 m/s, P=0.9). ConclusionBoth acute and short‐term supplementation with oral BH4 improved endothelial function but not aortic stiffness. This result suggests that BH4 supplementation may be beneficial for patients with rheumatoid arthritis by improving endothelial dysfunction and potentially reducing risk of cardiovascular disease. There appears to be no causal relationship between endothelial function and aortic stiffness, suggesting that they occur in parallel, although they may share common risk factors such as inflammation.